Проблематика оценки эффективности государственного финансирования социальных инвестиционных проектов (Путеводитель предпринимателя)
The theoretical approaches to economic-mathematical methods and models of the formation of economically viable rate of social discount rate, accounted in the problems of comparative analysis and selection of investment projects, social services, used by the federal budget. The conclusion about the need to use in determining the discount rate, a combined approach based on the consistent application of methods of economic-mathematical modeling and experimental evaluation obtained for a series ofsuccessiveperiods of the values of standard efficiency investments of federalfunds in the investment program of the regions.